Sjiele sacrifices, Odin treasures and Saami graves? - Zachrisson, Inger (Scripta Instituti Donneriani Aboensis, 1987)
This paper presents archaeological findings described as Saami metal deposits. These well-known "Finds from Lapp Places of Sacrifice", objects from the Viking Age and Early Middle Ages, were mostly found in northern Sweden. The author also presents a research project dealing with prehistoric and medieval Saami graves from the south Saami area.